Decrypting SSL traffic: best practices for security, compliance and productivity. Issue 8 (August 2019) - Taylor, Adrian
Abstract : Back in 2014, when Google's search engine started giving HTTPS sites a boost in their ranking algorithm, only 15% of websites worldwide used a valid SSL (secure socket layer) certificate. But Google recently reported that 94% of traffic across all its products and services is now encrypted. 1